Fulfilling customer needs in agribusiness supply chains - Batt, Peter (ISHS, 2006)
Concentration and aggregation in the retail sector is having a profound effect on horticulture worldwide. With consumers becoming more concerned about the integrity of the food they consume and the impact of intensive production on the environment, retailers must give much greater consideration towards product safety and product quality at all stages of the supply chain. While competition between the major supermarket chains is propounded as being the major force leading towards greater consolidation in the retail sector, it is argued that the requirement for retailers to exercise due diligence has had the most significant impact on the supply chain itself. Following an alarming increase in the incidence of food poisoning, most Governments have responded by enacting a raft of legislation which requires retailers to take all reasonable steps to ensure that the food they sell is safe. It also means that all upstream firms need to more carefully monitor the product and the way in which they handle it to satisfy their downstream customers. As a result, most retailers and food processors have taken extraordinary steps to institute stringent quality assurance programs with their suppliers, with particular emphasis on traceability. All major supermarkets now require fresh produce to be sourced from suppliers who have an accredited quality management system. A genuine and visible quality management program is now a prerequisite for any food company who wishes to supply the supermarkets.